Membangun Paradigma Hukum HAM Indonesia Berbasis Kewajiban Asasi Manusia - Paulus Rudy Calvin Sinaga; Anna Erliyana (Constitutional Court of the Republic of Indonesia, Indonesia, 2021)
Human rights are essential things to uphold because their existence guarantees the equality of all humanity. In Indonesia, the issue of human rights is still often a problem, and one source of the problem is the imbalance between human rights and unbalanced with human rights obligation. This research was conducted with a systematic literature review approach to propose a human rights law paradigm based on human rights obligations. From the perspective of legal analysis, the nature of this research is categorized into prescriptive research. The materials in this study were sourced from laws, books, and scientific articles from national and international journals that deal with the concept of human rights and human rights law. The results of this study indicate that the enforcement of human rights must look at fulfilling human rights obligations because, in general, a person can claim rights if they have met the requirements. By basing their rights on obligations, human rights law will improve. This article is expected to be able to be one of the references in the application of human rights law in Indonesia to build justice between human rights and obligations.